Pengaruh Pendapatan Asli Daerah (Pad) Dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Daerah (Studi Kasus Pemerintah Daerah Kabupaten/Kota Diy Tahun 2007-2013) - Prasasti, Swastika Enjang; Sari, Ratna Purnama (Akmenika, 2015)
The aim of this research is to test whether local own-source revenue (PAD) and the Fund Balance have an effect to goverment’s financial performance of regencies in DIY. This research was held for giving public administration, organizational theory and govermental accounting’s knowledge. This research also held based on the un optimal financial performance in order to adequate public’s need. The research is using budget realization report of DIY regency on 2007-2013 published by Dinas Perimbangan and using 30 samples of data. The data were analyzed by quantitative method and tested by multiple linear regression. The result shows that the local own-source revenue (PAD) and the Fund Balance giving a simultanouse effect on financial performance partially, local own-source revenue (PAD) has a positive significant effect wile fund balance has a negative significant effect on goverment’s financial performance of DIY.